A time-varying perspective on the CAPM and downside betas - Tsai, Hsiu-Jung; Chen, Ming-Chi; Yang, Chih-Yuan (International review of economics & finance, 2014)
In the current study, we focus on the capital asset pricing model (CAPM) beta and downside betas. The empirical results of market index returns in the international samples of 23 developed countries exhibit significant differences between the CAPM and downside betas, indicating that these models capture distinct risks. Considering autocorrelation variance, the DCC downside betas (HW-beta and HR-beta) more effectively explain the expected stock market returns than does the CAPM beta. •We use a DCC model to estimate the time-varying CAPM beta and downside betas.•The CAPM beta and downside betas capture different risks.•Downside betas explain the expected stock returns better than CAPM beta.